The effect of Korean wave on body image and eating disorders among female adolescents in Yogyakarta, Indonesia - Nurina Umy Habibah; A Fahmy Arif Tsani; Sumarni DW (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2021)
Background: Currently, Indonesia is one of the countries affected by the Korean